2012
DOI: 10.1097/hjh.0b013e3283576faf
|View full text |Cite
|
Sign up to set email alerts
|

High ambulatory blood pressure values associated with non-alcoholic fatty liver in middle-aged adults

Abstract: Significantly higher ambulatory daytime and night-time SBP levels were seen in individuals with fatty liver. Nondipping does not seem to associate with liver fat. The coexistence of liver fat accumulation and high BP are likely to potentiate the risk for cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…We found that adult measures of adiposity, triglycerides, insulin, systolic blood pressure, physical activity, and red meat consumption were on the pathway linking childhood SED with fatty liver. All these observed mediators have been previously associated with fatty liver . Adiposity and insulin resistance are considered key factors in the pathophysiology of fatty liver .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We found that adult measures of adiposity, triglycerides, insulin, systolic blood pressure, physical activity, and red meat consumption were on the pathway linking childhood SED with fatty liver. All these observed mediators have been previously associated with fatty liver . Adiposity and insulin resistance are considered key factors in the pathophysiology of fatty liver .…”
Section: Discussionmentioning
confidence: 95%
“…Adiposity and insulin resistance are considered key factors in the pathophysiology of fatty liver . Systolic blood pressure is also associated with fatty liver, but the mechanisms that explain the association that are independent of adiposity or insulin resistance remain unknown . In addition, physical inactivity and unhealthy dietary habits, especially high consumption of red meat, have been considered behavioral risk factors of fatty liver .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood pressure (BP), including systolic blood pressure (SBP) and diastolic blood pressure (DBP), is an important risk factor for developing NAFLD [7][8][9][10], even in individuals without hypertension [10]. Mean arterial pressure (MAP), a steady component of BP, has wildly been used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%